Identifying factors on bullying in school: qualitative analysis - Mohammad Narimani; Nima Sadeghzadeh Belil (مطالعات روانشناسی تربیتی, 2024)
Bullying is a complex behavioral problem that can be seen in most schools. The current research was conducted with the aim of identifying factors affecting bullying in school using qualitative analysis. This research is practical in terms of purpose and has been done using thematic analysis method. The sampling used in this research was cluster sampling with a purposeful sampling method. The main source of information gathering has been conducting in-depth interviews with experts, managers, teachers and experts in the field of education and research until reaching theoretical saturation. A total of 19 interviews were conducted. After collecting the data, the codes related to the written interviews were analyzed using thematic analysis method. The findings of the research, which is the final model of the research after three stages of open, central and selective coding. It shows that the factors affecting bullying in school with 66 codes and in 6 categories are individual factors, school factors, family factors, classroom issues, friends and peers, and environmental factors. By applying the identified factors, students can be taught skills to treat and reduce bullying in school so that they can use them to overcome their bullying.